Alinhamento da estratégia corporativa ao nível de serviço desejado pelos clientes por meio da aplicação do BSC e do Seis Sigma - Nunes Filho, Fernando Ribeiro de Melo (2012)
The focus of this dissertation is to study the alignment between corporate strategy and the service level desired by customers. Its main purpose is to develop a method that analyses the alignment between corporate strategy and the service level desired by customers and presents possible solutions to its improvement. The method of reasoning used in this dissertation was the hypothetical-deductive. Regarding the methodology for achieving the proposed objectives, it was used an applied research classified as qualitative, exploratory, bibliographical, documentary and case study. Strategy, strategic alignment, BSC, Six Sigma and logistics service level were the knowledge researched to substantiate the proposed method, which prioritizes the alignment based on BSC indicators and promotes improvements by the use of Six Sigma. The application of the method was performed in a hospital laundry that served as case study. The main conclusion of the study was the assessment of the usefulness of the proposed method in evaluating and improving the alignment of corporate strategy with service level desired by customers.